(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2015)
Arthropods with venom glands that are capable of inflicting accidents of medical significance in humans have been poorly studied in Ecuador from epidemiological, clinical or biochemical standpoints despite the high diversity of arthropods in general in the country. Severe accidents due to envenoming by scorpions (Tityus asthenes Pocock), spiders (Phoneutria Perty) and “conga” ants (Paraponera clavata (Fabricius) have taken place in the coastal and Amazonian regions which have been underestimated in sanitary importance probably due to its prevalence in rural settings. Accidents derived from bites by spiders in the genus Loxosceles Heinecken & Lowe and scolopendrids (Class Chilopoda, Order Scolopendromorpha) or by contact with venomous caterpillars (Order Lepidoptera) have not been reported in spite that several potentially toxic species inhabit Ecuador. This work reports on the results of a scientific seminar conducted at the Natural Sciences Faculty, Universidad de Guayaquil, which involved students from the School of Biology, with the goal to evaluate, for the first time, the current knowledge on selected venomous arthropods in Ecuador belonging to the classes Arachnida, Chilopoda and Insecta and including perspectives of research on these medically important taxa in Biotechnology and Evolution.